Exploring queer pedagogies in the college-level YA literature course. Issue 6 (1st November 2016) - Bach, Jacqueline
ABSTRACT: One place to start understanding how pre-service teachers learn about contemporary young adult (YA) literature, especially those works that feature lesbian, gay, bisexual, transgender, questioning (LGBTQ) and gender identity themes and characters, is through an examination of the YA literature course – a course many pre-service teachers take as part of their teacher certification programs in the USA. In this article, I turn to queer pedagogy to explore the syllabi of 67 college-level YA literature courses in order to address the question: 'How do young adult literature courses incorporate the growing body of high-quality young adult literature that features LGBTQ and gender variant themes and characters?' Findings include how the YA literature field might be normalizing, or standardizing through repeated approaches, what it means to teach a text and in turn shape future teachers' decisions on how a text is incorporated into a curriculum.